Deciphering p53 Signaling in Tumor Suppression - Mello, Stephano S. (Curr Opin Cell Biol, 2017)
The p53 transcription factor is mutated in over half of human cancers, and p53-null mice are highly predisposed to cancer, highlighting p53’s essential role in tumor suppression. Studies in mouse models have revealed that p53 cell cycle arrest and apoptosis responses to acute DNA damage signals are dispensable for tumor suppression, prompting a search for new mechanisms underlying p53-mediated cancer suppression. p53 responds to other types of stress signals and regulates a host other cellular processes, including maintenance of genomic stability, metabolism, stemness, non-apoptotic cell death, migration/invasion, and cell signaling, any or all of which could be fundamental for suppressing carcinogenesis. The ability of p53 to govern numerous transcriptional programs and cellular functions likely explains its potent tumor suppressor activity.